Intravenous Recombinant Tissue Plasminogen Activator in Acute Ischemic Stroke: Factors Affecting Clinical Outcomes - Hanif Mustikasari; Muvida Muvida; Limawan Susilo Nugroho (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke is one of the leading causes of disability and death worldwide. Thrombolytic therapy using intravenous recombinant tissue plasminogen activator (rt-PA) is the recommended treatment. However, functional outcomes vary due to various factors. Objective: The aim of this study was to analyze the factors affecting clinical outcomes of acute ischemic stroke patients treated with intravenous rt-PA. Method: This research was a retrospective study with a total sample of 52 acute ischemic stroke patients who received intravenous rt-PA therapy. The research variable data were collected from medical records, then statistically analyzed and correlated with patient clinical outcomes. Data from medical records were collected based on inclusion and exclusion criteria, then statistically analyzed using STATA 13. Univariate analysis is presented in a list of categories according to the research variables determined by percentage (standard error). Bivariate analysis was tested using simple logistic regression and multivariate analysis using multiple logistic regression. Results: The results of this study showed that patient clinical outcomes are not significantly impacted by risk factors (age, gender, prior stroke history, comorbidities), COVID-19 vaccination, onset and severity of stroke, HCTS onset, dosage, or onset therapy. The side effects of intravenous rt-PA have a significant impact on patient clinical outcomes, including therapy response and discharge condition (p = 0.008, p < 0.05, and p = 0.012, OR 34.073 (95% CI 2.165 – 536.147)), but do not affect the length of hospital stay. Conclusions: In considering the other factors, the study indicates that patients experiencing adverse effects from intravenous rt-PA have worse clinical outcomes.